Aesthetic experience and imagination in early elementary school science – a growth of 'Science–Art–Language–Game'. Issue 5 (24th March 2022) - Caiman, Cecilia; Jakobson, Britt
ABSTRACT: The purpose is to contribute knowledge to the field regarding the role of aesthetic experience when young students participate in intertwined science–art activities in science class. More precisely, we scrutinise how science suggestions are shaped in students' processes of imagination when exploring animal's ecology. Data corpus comprises audio recordings, photographs, drawings and field notes. The school is located in Sweden and the participating students were between 6 and 7 years old (Swedish grade 1). Seven students and their teacher participated in the study. The dialogues were analysed by means of a practical epistemology analysis (PEA), based on Dewey and the later Wittgenstein. In addition, the analytical term pictorial relation is launched to analyse the visual language exposed in students' drawings. The results reveal that throughout the process, the young students in transaction with the contextual features, imagined suggestions and solutions to science-related issues. Facts and fiction, sense and nonsense blended when new solutions of pleasurable hiding-places for prey were aesthetically and imaginatively explored and designed. In addition, the students owned the problem throughout and developed agency, which resulted in novel science–art outcomes and the students' communicative repertoire was extended when involved in intertwined dialogues and art activities.